STATUS GIZI ANAK BALITA BERDASARKAN UKURAN ANTROPOMETRI DI DESA SAMBIREJO KECAMATAN BINJAI - Riwayati Riwayati (JURNAL KELUARGA SEHAT SEJAHTERA, 2015)
ABSTRACTNutritional status is a state of the body as a result of food consumption and utilization of nutrients which can be distinguished between poor, less, better, and more nutritional status. Consumption of food affects the nutritional status of a person. Good nutritional status occurs when the bodies are getting enough nutrients. Nutritional status can be determined based on anthropometric measurements. This study aims to determine the nutritional status of children under five years of age by size anthropometry. This study used a cross-sectional approach which was a type of research that emphasized the time measurement/observation data was only one variable at a time. The data collected was qualitative data in the form of education and employment levels. While quantitative data was the height and weight of children under five years of age. The data were collected through observation and interviews. Nutritional status data were obtained by measuring body weight (BW) and height (TB) using the scale and mikrotoa conducted by researchers. Measurement of nutritional status with the index BW/TB considered normal if -2 s/d +2 SD, wasthing -3 s/d < -2 SD, very thin < -3SD, obese > +2 SD. The results shows that the majority (45%) of children have normal nutritional status, 30% of children have nutritional satus wasthing, 5% of children have a very low nutritional status and 20% of obese children have nutritional status.